Global trends and future predictions of gastrointestinal ulcers in youth - He, Kun; Ye, Shicai; Kou, Yanqi; Du, Shenshen; Yuan, Weinan; Ge, Lei; Tian, Yuan; Luo, Botao; Ha, Yanping; Zhan, Liping; Ye, Ruyin; Huang, Yujie; et al. (Frontiers in Public Health, 2025)
BackgroundBy analyzing past disease trends and comparing two time series statistical models, we can predict the global burden of gastrointestinal ulcers in specific populations of adolescents and young adults aged 10–24. This prediction can provide important references for optimizing prevention and control strategies in healthcare systems.MethodsWe collected data on prevalence, incidence, disability-adjusted life years (DALYs), and mortality for specific age groups between 10 and 24 years from 1990 to 2019. The data were then stratified by age, gender, and economic development level. We applied decomposition analysis and frontier analysis, and compared the performance of two statistical prediction models. We used the best-performing model to predict changes in each indicator.ResultsIn 2019, there were 958,842 (95% uncertainty interval [UI]: 639,698–1,371,106) prevalent cases, 407,850 (95% UI: 260,513–577,751) incident cases, 363,862 (95% UI: 309,793–422,230) DALY cases, and 4,404 (95% UI: 3,826–5,042) deaths globally, all showing an increasing trend compared to 1990. However, the age-standardized prevalence rate (ASPR), age-standardized incidence rate (ASIR), age-standardized DALY rate (ASDR), and age-standardized death rate (ASDER) all decreased from 1990 to 2019, with reductions of 6.6, 3.8, 50.86, and 53.8%, respectively. The estimated annual percentage change (EAPC) for these metrics was −0.59 (95% confidence interval [CI]: −0.73 to −0.46), −0.41 (95% CI: −0.51 to −0.31), −2.81 (95% CI: −2.96 to −2.66), and −3.1 (95% CI: −3.28 to −2.92), respectively. The ARIMA model, identified as the most accurate prediction model, suggests that by 2050, the burden of gastrointestinal ulcers in this age group will significantly decrease compared to 2019. Over the next 30 years, the global number of incident cases will initially rise before stabilizing, prevalent cases will fluctuate, and both DALYs and deaths will decline. ASPR, ASIR, ASDR, and ASDER will continue to decrease, with the most notable reductions in ASDR and ASDER.ConclusionIn 2019, the global burden of gastrointestinal ulcers showed significant increases in prevalent and incident cases, DALYs, and deaths compared to 1990. However, when adjusted for age, the prevalence rate (ASPR), incidence rate (ASIR), DALY rate (ASDR), and death rate (ASDER) all demonstrated substantial reductions, indicating improvements in management and prevention. The ARIMA model, identified as the most accurate, projects a significant decline in the burden of gastrointestinal ulcers for this age group by 2050, compared to 2019. While the raw numbers of cases and mortality have risen, age-standardized rates have decreased, reflecting advancements in healthcare strategies. These findings emphasize the need for continued focus on preventive measures and healthcare optimization to further reduce the global burden of gastrointestinal ulcers. The projected decline highlights the potential effectiveness of current strategies and offers a positive outlook for future management.